2003
DOI: 10.1002/ptr.1399
|View full text |Cite
|
Sign up to set email alerts
|

Screening South Indian medicinal plants for antifungal activity against cutaneous pathogens

Abstract: In this study, twenty-eight South Indian medicinal plants were screened for their anti-fungal activity against six species of fungi (Trichophyton mentagrophytes, T. rubrum, T. soudanense, Candida albicans, Torulopsis glabrata, and C. krusei). Three plant species extracts, Celastrus paniculatus, Eriodendron anfractuosum and Ficus glomerata showed inhibitory activity. An aqueous extract of galls of Terminalia chebula showed inhibitory effects on three dermatophytes (Trichophyton spp.) and three yeasts (Candida s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…Pre-treatment with T. cordifolia was to impart protection against mortality induced by intraabdominal sepsis following coecal ligation in rats (Singh et al 2003). C. paniculatus exhibited anti-fungal activity against six species of fungi (Trichophyton mentagrophytes, T. rubrum, T. soudanense, C. albicans, Torulopsis glabrata and C. krusei (Vonshak et al 2003). The aqueous extract of C. paniculatus seed has cognitiveenhancing properties and an antioxidant effect (Kumar and Gupta 2002).…”
Section: Resultsmentioning
confidence: 98%
“…Pre-treatment with T. cordifolia was to impart protection against mortality induced by intraabdominal sepsis following coecal ligation in rats (Singh et al 2003). C. paniculatus exhibited anti-fungal activity against six species of fungi (Trichophyton mentagrophytes, T. rubrum, T. soudanense, C. albicans, Torulopsis glabrata and C. krusei (Vonshak et al 2003). The aqueous extract of C. paniculatus seed has cognitiveenhancing properties and an antioxidant effect (Kumar and Gupta 2002).…”
Section: Resultsmentioning
confidence: 98%
“…Thus there is an urgent need for safer and more effective antifungal agents, and considerable resources are being channelled into the search for new agents (Dannaoui et al, 2001). Much effort has been undertaken in the area of medicinal plants to obtain therapeutic agents from natural sources (Vonshak et al, 2003). Diospyros is numerically and economically the most important genus of Ebenaceae, many species of which have been reported to exhibit interesting biological activities (Masami et al, 2003;Adeniyi et al, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…In addition, a prodrug activity for treatment of cardiovascular disorders has been described (9)(10)(11)(12)(13)). An aqueous seed extract of Terminalia chebula Retzius (TcRSE) exhibits in vitro antioxidant and free radical-scavenging behavior, and has potent antimicrobial, anticancer, antiviral, and anti-diabetic effects either in vitro or in vivo (14).…”
Section: Discussionmentioning
confidence: 99%
“…Terminalia chebula Retzius is an ethnopharmacological plant of India and Southeast Asia, and has traditionally been used as a laxative, a diuretic, and an anti-oxidative material (4)(5)(6)(7)(8). In addition, plant extracts have antibacterial (9,10), antiviral (11), antifungal (12) and immune modulatory activities (13,14). Recently, Lee et al (5,15) reported that an aqueous seed extract of Terminalia chebula Retzius (TcRSE) had potent anti-oxidant activity both in vitro and in vivo when tested as a hepatoprotective agent in an animal model.…”
Section: Introductionmentioning
confidence: 99%